Pengaruh Audit Tenure, Entrenchment Effect, dan Financial Distress Terhadap Kualitas Audit Dengan Komite Audit Sebagai Variabel Moderasi: Studi Empiris Pada Perusahaan BUMN Yang Terdaftar di BEI Tahun 2021-2024 - Fianti, Finka Rahma Dita; Agustin, Beby Hilda; Selviasari, Rike (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
Audit quality plays an important role in ensuring the reliability and credibility of financial statements, particularly in State-Owned Enterprises (SOEs) that are subject to high public accountability. This study aims to analyze the effect of audit tenure, entrenchment effect, and financial distress on audit quality, as well as to examine the moderating role of the audit committee in these relationships. The research employed a quantitative approach using secondary data obtained from annual reports, independent auditor reports, and ownership structure reports of State-Owned Enterprises listed on the Indonesia Stock Exchange during the 2021–2024 period. The sample was selected using purposive sampling, resulting in 20 companies with a total of 80 observations. Data were analyzed using logistic regression analysis and moderated regression analysis through interaction testing to evaluate the moderating effect of the audit committee. The results indicate that audit tenure does not have a significant effect on audit quality. In contrast, entrenchment effect and financial distress significantly affect audit quality. Furthermore, the audit committee is unable to moderate the relationship between audit tenure and audit quality as well as between financial distress and audit quality. However, the audit committee significantly moderates the relationship between entrenchment effect and audit quality. These findings suggest that audit quality in SOEs is more influenced by ownership dominance and financial conditions than by the duration of the auditor-client relationship. The study contributes to the literature on audit quality determinants and highlights the importance of strengthening corporate governance mechanisms through effective audit committee oversight.